1989
DOI: 10.2165/00003088-198916030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Differences in Bioavailability of Medroxyprogesterone Acetate Preparations

Abstract: Synthetic progestational agents first became widely available in the early 1960s and were investigated for use in patients with hormoneresponsive tumours, i.e. breast, kidney, uterine and prostate cancer. A range of different preparations was available, but their clinical use was limited by side effects including nausea and vomiting, masculinisation, Cushingoid effects and liver damage (Stoll 1967). An early study (Stoll 1967) of 6 orally active agents, including medroxyprogesterone acetate (MPA), concluded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…MPA exhibits low oral bioavailability ( < 10%), which may be due to numerous factors, including metabolism in the intestinal mucosa and liver (Stockdale and Rostom, 1989). In fact, MPA has been shown to undergo extensive and rapid metabolism in humans (Stockdale and Rostom, 1989) and in experimental animals (Rautio et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPA exhibits low oral bioavailability ( < 10%), which may be due to numerous factors, including metabolism in the intestinal mucosa and liver (Stockdale and Rostom, 1989). In fact, MPA has been shown to undergo extensive and rapid metabolism in humans (Stockdale and Rostom, 1989) and in experimental animals (Rautio et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, MPA has been shown to undergo extensive and rapid metabolism in humans (Stockdale and Rostom, 1989) and in experimental animals (Rautio et al, 1985). Recently, we reported that MPA was metabolized by cytochrome P450 3A4 (CYP3A4) in human liver microsomes (Kobayashi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%